Challenges of Marketing in COVID-19 Scenario: A Neuro-marketing Approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The findings in the areas of neuormarketing are just like a lightning strike for the marketers all over the world, as a matter of fact if the purchase behavior of a person can be identified facial expressions and body language; it is going to work like a breakthrough in the field of sales and marketing. The result can be in the form of product and service customization and more creative and dedicated promotion campaigns. These neuromarketing will be affected by this pandemic of COVID-19 but in a short term. Process of studies can be followed and even sampling can be enhanced in the process. This present study will evaluate the scenario of customer preference and behavior in pre and post COVID-19 period. The findings of this present study state that some significant changes has been observed in customer preferences due to the outbreak of COVID-19, but the changes are not significant enough to bring about major changes in the strategic patterns; rather the researcher would like to suggest that the marketers should explore some new dimensions for attracting the customer. This study is based on primary data and the results are analyzed by using SPSS ver. 23.0.